Population health a primer - Riegelman, Richard K. (Jones & Bartlett Learning, 2020)
"Population health is rapidly becoming an overarching umbrella for connecting the clinical health professions, traditional public health, and health administration and policy. Population Health: A Primer for the Health Professions provides an overview of population health including key concepts and approaches needed to build an educational foundation for this rapidly emerging field.The text begins with an overview of population health and why it matters before providing a step-by-step approach to thinking in systems and covering the basic tools of population health. Case studies throughout illustrate the application of approaches for addressing population health issues. A helpful instructor's guide suggests options for using the Primer in short courses, as part of a larger course, or as individual units"--Provided by publisher.